Virtual Embodiment of White People in a Black Virtual Body Leads to a Sustained Reduction in Their Implicit Racial Bias - Banakou, Domna; Hanumanthu, Parasuram D.; Slater, Mel (Frontiers in Human Neuroscience, 2016)
Virtual reality can be used to visually substitute a person's body by a life-sized virtual one. Such embodiment results in a perceptual illusion of body ownership over the virtual body (VB). Previous research has shown that the form of the VB can influence implicit attitudes. In particular, embodying White people in a Black virtual body is associated with an immediate decrease in their implicit racial bias against Black people. We tested whether the reduction in implicit bias lasts for at least 1 week and whether it is enhanced by multiple exposures. Two experiments were carried out with a total of 90 female participants where the virtual body was either Black or White. Participants were required to follow a virtual Tai Chi teacher who was either Asian or European Caucasian. Each participant had 1, 2, or 3 exposures separated by days. Implicit racial bias was measured 1 week before their first exposure and 1 week after their last. The results show that implicit bias decreased more for those with the Black virtual body than the White. There was also some evidence of a general decrease in bias independently of body type for which possible explanations are put forward.